Carbon Isotope Composition and Geochemical Features of Sediments From Gongga Mountain, China, and Potential Environmental Implications - Wu, Yingqin; Wang, Tong; Liu, Yan; Ma, Rong; Chen, Zhangxin (Frontiers in Earth Science, 2022)
Using gas chromatography-triple quadrupole tandem mass spectrometry (GC-MS/MS), the soluble organic matter was analyzed for the first time in twenty-two sediment samples from the eastern slopes of the Gongga Mountain, China, at high altitudes between 4,600m and 6,700m. The C11-C33 n-alkanes and C9-C33 n-alkan-2-ones were identified in these samples. Both compounds were dominated by odd carbon numbers in the long-chain molecules and contained a maximum of n-C27 or n-C29, indicating that the sediments were predominantly of higher plant origin. However, the short-chain n-alkan-2-ones, with a maximum content of n-C17 or i-C18 (phytone, 6, 10, 14-trimethylpentadecan-2-one), did not show a predominance of odd and even numbers, suggesting that they were predominantly derived from bacteria and algae. Therefore, we suggest that the organic matter in Gongga Mountain comes from three sources, i.e. bacteria, algae, and higher plants. Stable carbon isotope (δ13C) values ranged from -24.6‰ to -27.3‰, indicating that C3 plants were the dominant organic input to the sediments and suggesting a relatively colder and drier depositional environment. However, C4 plants increase sharply at high altitudes of 6,300 to 6,600 m, suggesting that the paleoclimate of Gongga Mountain became drier and wetter with the increase of altitude.